A common mechanism of clinical HIV-1 resistance to the CCR5 antagonist maraviroc despite divergent resistance levels and lack of common gp120 resistance mutations - Roche, M.; Salimi, H.; Duncan, R.; Wilkinson, B.; Chikere, K.; Moore, M.; Webb, N.; Zappi, H.; Sterjovski, J.; Flynn, J.; Ellett, A.; Gray, L.; et al. (2013)
Background: The CCR5 antagonist maraviroc (MVC) inhibits human immunodeficiency virus type 1 (HIV-1) entry by altering the CCR5 extracellular loops (ECL), such that the gp120 envelope glycoproteins (Env) no longer recognize CCR5. The mechanisms of HIV-1 resistance to MVC, the only CCR5 antagonist licensed for clinical use are poorly understood, with insights into MVC resistance almost exclusively limited to knowledge obtained from in vitro studies or from studies of resistance to other CCR5 antagonists. To more precisely understand mechanisms of resistance to MVC in vivo, we characterized Envs isolated from 2 subjects who experienced virologic failure on MVC.Results: Envs were cloned from subjects 17 and 24 before commencement of MVC (17-Sens and 24-Sens) and after virologic failure (17-Res and 24-Res). The Envs cloned during virologic failure showed broad divergence in resistance levels, with 17-Res Env exhibiting a relatively high maximal percent inhibition (MPI) of ~90% in NP2-CD4/CCR5 cells and peripheral blood mononuclear cells (PBMC), and 24-Res Env exhibiting a very low MPI of ~0 to 12% in both cell types, indicating relatively " weak" and " strong" resistance, respectively.Resistance mutations were strain-specific and mapped to the gp120 V3 loop. Affinity profiling by the 293-Affinofile assay and mathematical modeling using VERSA (Viral Entry Receptor Sensitivity Analysis) metrics revealed that 17-Res and 24-Res Envs engaged MVC-bound CCR5 inefficiently or very efficiently, respectively. Despite highly divergent phenotypes, and a lack of common gp120 resistance mutations, both resistant Envs exhibited an almost superimposable pattern of dramatically increased reliance on sulfated tyrosine residues in the CCR5 N-terminus, and on histidine residues in the CCR5 ECLs. This altered mechanism of CCR5 engagement rendered both the resistant Envs susceptible to neutralization by a sulfated peptide fragment of the CCR5 N-terminus.Conclusions: Clinical resistance to MVC may involve divergent Env phenotypes and different genetic alterations in gp120, but the molecular mechanism of resistance of the Envs studied here appears to be related. The increased reliance on sulfated CCR5 N-terminus residues suggests a new avenue to block HIV-1 entry by CCR5 N-terminus sulfopeptidomimetic drugs.